Temper-treatment development to decompose detrimental martensite–austenite and its effect on linepipe welds. Issue 16 (2nd November 2017) - Huda, Nazmul; Ding, Yuquan; Gerlich, Adrian P.
ABSTRACT: A tempering cycle was developed via heat treatment to study the decomposition of detrimental martensite–austenite (MA). The heat treatment cycle was found to preferentially decompose hard MA with a critical size of ≥1 µm, which decreases the hardness of these microconstituents after tempering at 300°C for 10 min. The dislocation density inside the MA and in the surrounding matrix was also decreased. Tempering of the X80 weldments containing MA reveals a similar decomposition behaviour. During transverse weld tensile testing of welds, a fracture occurred in the heat-affected zone due to void formation at the MA/ferrite interfaces. However, a fracture occurred in base metal with improved strength and ductility after tempering, in comparison to the fracture in the heat-affected zone of as-welded samples.